Revision Surgery for Degenerative Spine Disease in Low Income Countries: A Growing Challenge in Resource Limited Neurosurgical Settings - ul Haq, Mian Iftikhar; Hussain, Shafaat; Siddique, Mudassar Abbas; Qureshi, Amjad Ali; Kumar, Pavan (Journal of Neonatal Surgery, 2024)
Background: Surgery for degenerative spinal illnesses is revision surgery is common nowadays, but is also very difficult in low-income countries due to limited imaging, implants, and post-operative infrastructure. Patients frequently show up late, have complicated pathologies, and have unsuccessfully undergone prior first-stage surgeries, thereby greatly complicating the revision surgeries. Objectives: To evaluate the clinical, radiological, and functional outcomes of revision spine surgery in a resource-limited neurosurgical setting and to compare recovery patterns between cervical and lumbar revision cases. Methods: An observational study spanning one year was performed on 82 patients receiving revision surgeries due to degenerative diseases of the spine. The demographic details, information on the operative variables, complications, and the VAS and ODI scores recorded preoperatively and postoperatively were documented and then compared between the cervical (Group A) and lumbar (Group B) cohorts. Results: Following the surgical procedures, there were no major differences in length of surgery, complications, functioning outcomes, or degree of operative disability, yet, both groups of participants showed strong decreases in the disability and pain operative scores. In case of lumbar revisions, there were higher percentages of operating recurrent disc herniation, and with the other named reasons there were pseudarthrosis and adjacent segment operated disease in both of the groups. Conclusion: Revision spine surgery provides meaningful improvements in pain and functional recovery even in low-resource environments. With careful case selection and standardized perioperative practices, outcomes comparable to higher-income regions can be achieved despite limited infrastructure..